2012
DOI: 10.1016/j.farma.2010.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization study in pediatric prescriptions of a university hospital in southern brazil: off-label, unlicensed and high-alert medications

Abstract: Frequency of unlicensed and off-label drug prescriptions showed in the study is according to the literature and may be considered high. High-alert drugs, although low in frequency, can present risks due to the harmful effects they can produce in patients. Thus, the highlighted drugs in this study constitute a constant concern in hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 24 publications
3
36
0
6
Order By: Relevance
“…Observing the profile of oral solutions and suspensions compounded for newborns and children of the studied hospital, it was verified that solutions/suspensions of these active principles were identified in other studies: folic acid,9 , 19 folinic acid,9 , 20 ursodeoxycholic acid,11 , 14 captopril,8 , 9 , 14 , 15 , 18 , 21 caffeine,12 , 16 , 19 , 22 , 23 spironolactone,9 , 24 - 28 fluconazole,17 furosemide,8 , 9 , 26 hydrochlorothiazide,8 , 9 , 18 , 26 , 27 propranolol,10 ranitidine,9 pyrimethamine17 and sulfadiazine 17. Therefore, it is observed that the demand for oral solutions and suspensions administered to newborns and children in this study has also been observed in other studies and that the compounding of drugs is a national and international necessity due to the lack of oral liquid drugs from the pharmaceutical industry.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Observing the profile of oral solutions and suspensions compounded for newborns and children of the studied hospital, it was verified that solutions/suspensions of these active principles were identified in other studies: folic acid,9 , 19 folinic acid,9 , 20 ursodeoxycholic acid,11 , 14 captopril,8 , 9 , 14 , 15 , 18 , 21 caffeine,12 , 16 , 19 , 22 , 23 spironolactone,9 , 24 - 28 fluconazole,17 furosemide,8 , 9 , 26 hydrochlorothiazide,8 , 9 , 18 , 26 , 27 propranolol,10 ranitidine,9 pyrimethamine17 and sulfadiazine 17. Therefore, it is observed that the demand for oral solutions and suspensions administered to newborns and children in this study has also been observed in other studies and that the compounding of drugs is a national and international necessity due to the lack of oral liquid drugs from the pharmaceutical industry.…”
Section: Discussionsupporting
confidence: 63%
“…, 8 Costa et al found 119 drug adaptations from solid to liquid form and Gavrilov et al identified two dose modifications in pharmaceutical forms 910 Dos Santos and Heineck found that 79 prescription items involved extemporaneous preparations 11. Extemporaneous compounded oral preparations are magistral drugs that should be used within 48hours 3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were conducted in 18 countries spread across four continents, principally Europe (55.9 %) [19-23, 25, 28-30, 32, 35, 37-39, 41, 43, 44, 48, 49], followed by America (23.5 %) [27,31,34,40,45,47,50,52], Asia (11.8 %) [24,33,36,42,46] and Oceania (5.9 %) [26,51]. The country with most studies was Brazil (14.7 %) [27,34,45,47,50].…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…Quando avaliadas as classes ATC, verificou-se que a mais prescrita incluiu os medicamentos para o sistema nervoso, seguida de anti-infecciosos sistêmicos e dos medicamentos para trato digestivo e metabólico; e comparativamente a outros estudos, verificou-se uma semelhança nas classes mais utilizadas [10,[44][45][46]. Os anti-infecciosos sistêmicos aparecem na lista dos medicamentos mais utilizados por crianças em diversos estudos [47,48], e este é um resultado esperado ao considerar-se que as doenças infecciosas, especialmente as de vias respiratórias, estão entre as morbidades mais comuns em crianças, sendo responsáveis por grande parte das prescrições de antimicrobianos [49].…”
Section: Artigo Originalunclassified